An Internal Promoter Drives the Expression of a Truncated Form of CCC1 Capable of Protecting Yeast from Iron Toxicity - Catarina Amaral; Cristina Teixeira Vicente; Soraia Marques Caetano; Ana Gaspar-Cordeiro; Yang Yang; Peter Cloetens; Célia V. Romão; Claudina Rodrigues-Pousada; Catarina Pimentel (Microorganisms, 2021)
In yeast, iron storage and detoxification depend on the Ccc1 transporter that mediates iron accumulation in vacuoles. While deletion of the CCC1 gene renders cells unable to survive under iron overload conditions, the deletion of its previously identified regulators only partially affects survival, indicating that the mechanisms controlling iron storage and detoxification in yeast are still far from well understood. This work reveals that CCC1 is equipped with a complex transcriptional structure comprising several regulatory regions. One of these is located inside the coding sequence of the gene and drives the expression of a short transcript encoding an N-terminally truncated protein, designated as s-Ccc1. s-Ccc1, though less efficiently than Ccc1, is able to promote metal accumulation in the vacuole, protecting cells against iron toxicity. While the expression of the s-Ccc1 appears to be repressed in the normal genomic context, our current data clearly demonstrates that it is functional and has the capacity to play a role under iron overload conditions.